Economic Recovery: A Bibliometric Study - Rindy Dwi Ladista (Studi Ekonomi dan Kebijakan Publik, 2023)
Purpose: This study aims to determine the characteristics of previous studies on economic recovery Research Methodology: This research is a bibliometric study using the charting the field method developed by Hesford et al., (2006). Results: 46 articles from 2021-2022 were obtained from the Sinta accredited journal with the keyword economic recovery. The majority articles are from 2021, Sinta 5, economic journal, used qualitative research, secondary data sources. Last, three strategies most discussed were empowerment of MSMEs, the provision of social assistance, and the use of Islamic financial instruments. Limitations: This study uses only two of the three classifications developed by Hesford et al (2006). Contribution: The novelty in this research is to propose a new classification based on the focus and scope of journals, Sinta's accreditation rating, types of research, types of data sources, data collection methods, and economic recovery strategies discussed.